Large seasonal and interannual variations of biogenic sulfur compounds in the Arctic atmosphere (Svalbard; 78.9° N, 11.9° E) - S. Jang; K.-T. Park; K. Lee; Y. J. Yoon; K. Kim; H. Y. Chung; E. Jang; S. Becagli; B. Y. Lee; R. Traversi; K. Eleftheriadis; R. Krejci; et al. (Atmospheric Chemistry and Physics, 2021)
Seasonal to interannual variations in the concentrations of sulfur aerosols ( < 2.5 µ m in diameter; non sea-salt sulfate: NSS-SO <msubsup>42-</msubsup> <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="277c1427ed297c2e5c45f7f988764cfe"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-9761-2021-ie00001.svg" width="13pt" height="17pt" src="acp-21-9761-2021-ie00001.png"/></svg:svg> anthropogenic sulfate: Anth-SO <msubsup>42-</msubsup> <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="4a53e7d1f00f4334c934356877052515"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-9761-2021-ie00002.svg" width="13pt" height="17pt" src="acp-21-9761-2021-ie00002.png"/></svg:svg> biogenic sulfate: Bio-SO <msubsup>42-</msubsup> <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="972fd8e8ae3fad8e22756ca8f92061a6"><svg:image ...